Graphicacy and the third dimension: an investigation into the problem of poor performance in relief mapwork in South African secondary schools - Burton, Michael St. John Whitehead (Rhodes University, Faculty of Education, Department of Education, 1986)
Three-dimensional graphicacy is the part of map work that appears to be the most problematIcal. Bartz (1970) says that thinking and visualising in three-dimensional space is difficult enough, but trying to derive notions in three-dimensions, when you have only seen them as they are represented in distorted two-dimensional fashion, is even more difficult. Yet pupils of geography are required to learn such three-dimensional concepts from the two-dimensional distorted map presentations. The geography teacher has an important educational role to play in promoting graphicacy and Balchin (1965), who coined the term, felt that it should be an essential underpinning of an integrated education. The problem is that children perform badly, teachers are not successfully imparting three-dimensional graphicacy skills and as Board and Taylor (1977) indicate, for some time now it has been fashionable to dismiss maps as being irrelevant or useless in geographical research. This thesis attempts to analyse this reported malady, the problems are exposed and solutions offered. Investigation of the literature, with the aim of clarifying the problems involved, follows four leads. These are the part played by the map as a mode of communication, the physical processes involved in mapwork revealed by work in the realm of neurophysiology, the process of visualisation in the field of perception and psychology, and finally the stage of conceptual development of the mapworker. The state of affairs in South Africa is disclosed by an analysis of teacher-directed literature, of examination syllabuses, of text-book treatment of three-dimensional mapwork in South Africa and overseas, of past examination questions, and finally of teachers' views. Experimental exercises have been executed in an attempt to link the key findings of published research to the local scene. Conclusions are then drawn, and recommendations made for improving three-dimensional graphicacy in South African secondary schools.
Keywords: Graphicacy; Maps; Map reading; Visualisation; Geography; Secondary education -- South Africa; Pupils; Learners; Teachers